2003
DOI: 10.1055/s-2003-42416
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for the Chemoselective Preparation of Benzoylated 1,2-Diols from Epoxides

Abstract: A very efficient and highly regioselective ring-opening reaction of epoxides with benzoic acid and its derivatives in the presence of cat. amount of tetrabutylammonium bromide (TBAB) in anhydrous acetonitrile has been developed. This effective method is useful for the preparation of selectively protected diols as precursor for many organic syntheses such as those of acyclic nucleosides and other synthetic purposes. The advantages of this method are efficiency, selectivity, low cost, and the applicability in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 6 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Nevertheless, there are some reports of comparable reactions with epoxide moieties and carboxylic acids, which took place under metal-mediated catalysis. The reported catalysts for the ring-opening reactions of epoxides initiated by carboxylic acids are generally limited to Lewis acid catalysts, such as FeCl 3 , tetrabutylammonium chloride and bromide, and Ce(OTf) 4 [18][19][20][21]. In the case of glycidol, the combination of the high ring strain of the epoxide and the polarity of the carbon-oxygen bonds makes the ring prone to nucleophilic attack.…”
Section: Modification Of Hpes 1 To Uniform Diol Endgroupsmentioning
confidence: 99%
“…Nevertheless, there are some reports of comparable reactions with epoxide moieties and carboxylic acids, which took place under metal-mediated catalysis. The reported catalysts for the ring-opening reactions of epoxides initiated by carboxylic acids are generally limited to Lewis acid catalysts, such as FeCl 3 , tetrabutylammonium chloride and bromide, and Ce(OTf) 4 [18][19][20][21]. In the case of glycidol, the combination of the high ring strain of the epoxide and the polarity of the carbon-oxygen bonds makes the ring prone to nucleophilic attack.…”
Section: Modification Of Hpes 1 To Uniform Diol Endgroupsmentioning
confidence: 99%
“…5 In contrast to the chemo-and region-selective ring opening of terminal epoxides with carboxylic acids, there are few reports on the asymmetric ring opening (ARO) of racemic epoxides using carboxylic acid as a nucleophile. [5][6][7][8][9] A previous study showed that chiral cobalt-salen complexes displayed good reactivity and high enantioselectivity for monoester synthesis via the EKR reaction. 10 Because chiral cobalt-salen complexes are very active and enantioselective catalysts in ARO reactions, 11 they are excellent candidates for the covalent attachment of homogeneous ligands to polymeric or inorganic supports.…”
Section: Introductionmentioning
confidence: 99%
“…1, CH 1, CH 2, and CH 3 have photochemically active C=C double bonds those are cross-linkable by irradiation of radical initiators [9][10][11][12]. In those polymers, reactive methacrylate side chains have various side chain lengths, and also various densities in the main chains (ratios of x and y were set to 1:1, 4:1, or 10:1).…”
Section: Introductionmentioning
confidence: 99%